2010
DOI: 10.1074/jbc.m109.095505
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Identification of Carnosine Synthase as ATP-grasp Domain-containing Protein 1 (ATPGD1)

Abstract: Carnosine (␤-alanyl-L-histidine) and homocarnosine (␥-aminobutyryl-L-histidine) are abundant dipeptides in skeletal muscle and brain of most vertebrates and some invertebrates. The formation of both compounds is catalyzed by carnosine synthase, which is thought to convert ATP to AMP and inorganic pyrophosphate, and whose molecular identity is unknown. In the present work, we have purified carnosine synthase from chicken pectoral muscle about 1500-fold until only two major polypeptides of 100 and 90 kDa were pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
149
0
14

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 175 publications
(165 citation statements)
references
References 37 publications
2
149
0
14
Order By: Relevance
“…At the indicated times, an aliquot (200 l) was taken; 100 l of the reaction mixture were loaded onto a 1-ml Dowex AG1-X8 (Cl Ϫ form) to assay radiochemically glutamate consumption and NAAG formation (see "Material and Methods"), and 100 l were used to measure nucleotides by high pressure liquid chromatography as described in Ref. 34. Values are means of three measurements using two and three independent preparations of RIMKLA and RIMKLB, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…At the indicated times, an aliquot (200 l) was taken; 100 l of the reaction mixture were loaded onto a 1-ml Dowex AG1-X8 (Cl Ϫ form) to assay radiochemically glutamate consumption and NAAG formation (see "Material and Methods"), and 100 l were used to measure nucleotides by high pressure liquid chromatography as described in Ref. 34. Values are means of three measurements using two and three independent preparations of RIMKLA and RIMKLB, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, other methods, such as stimulation of carnosine synthesis and/or suppression of its degradation by a method of molecular biology, may be effective. In particular, carnosine synthase was recently identified in chickens (Drozak et al, 2010) and this may make molecular studies easier to perform. Further studies are needed to determine how to increase dipeptides in broilers.…”
Section: Discussionmentioning
confidence: 99%
“…Not only that, carnosine seems to contribute to the nutritional quality of meat because dietary carnosine has a hypoglycemic effect (Yamano et al, 2001), hypotensive action (Niijima et al, 2002), antidepressant-like activity (Tomonaga et al, 2008), and anti-aging effects (Gallant et al, 2000). Carnosine is synthesized from β-alanine (β-Ala) and histidine (His) by carnosine synthase (Drozak et al, 2010), and anserine is mainly formed from carnosine by a methylation reaction (Boldyrev and Severin, 1990), while Horinishi et al (1978) reported that a purified enzyme from chickens could methylate His to generate anserine by direct synthesis. On the other hand, carnosinase, which hydrolyzed carnosine or anserine to its constituent amino acids, was confirmed to be present in rats and humans.…”
Section: Introductionmentioning
confidence: 99%
“…For example, carnosine synthetase uses both, beta-alanine and GABA to synthesize carnosine and homocarnosine, respectively (44). Moreover, using purified carnosine synthetase, Drozak et al (35) could show that the enzyme, which also belongs to the ATP-grasp domain family, accepts different amino acids or amines as the second substrate. The physiological relevance of the additional NAAGS products, if produced at all in vivo, remains to be determined.…”
Section: Discussionmentioning
confidence: 99%